Utilization of Organic and Plastic Waste as Solid Fuel for Steam Power Plants 3 Parit Baru Site Bengkayang - Nurfitri Wulandari; Arifin Arifin; Govira Christiadora Asbanu (Universitas Diponegoro, 2024)
The problem of organic and non-economic LDPE plastic waste, which is abundant in the Singkawang City landfill, is accompanied by the reduced availability of coal as a fuel for steam power plants. Therefore, this study utilizes organic and plastic waste as biomass fuel that can be used in steam power plants using the co-firing method. This research aims to identify the characteristics, analyze the optimal composition based on SNI 8966:2021, and examine the influence of solid fuel composition. The research method used four composition variations: 100:0%, 95:5%, 85:15%, and 75:25. The best average water content, volatile matter, ash, fixed carbon, and calorific value were 4%, 60.67%, 11.33%, 2.67%, and 5,374.29 Kcal/kg, respectively. The characteristics of the solid fuel comply with SNI 8966:2021, except for the fixed carbon content. Based on the Kruskal-Wallis test, the fuel compositions for the characteristics of water content, volatile matter, ash, and calorific value are significantly different, with values of 0.035, 0.056, 0.041, and 0.016. Based on Spearman rank correlation analysis, water and ash contents decreased as the percentage of plastic increased, with correlation coefficients of -0.753 and -0.302. Meanwhile, the calorific value and volatile matter increased, with correlation coefficients of 0.811 and 0.972.